PHYSICAL EDUCATION IN THE DEVELOPING STATES IN THE PACIFIC (Fiep Bulletin - online, 2013)
There are twenty-two island countries and territories in Oceania dispersed over 30 million km of the Pacific Ocean. Eight million people live in the Pacific. The broad ethnic groups are Melanesian, Polynesian and Micronesian. New Zealand and Australia have strong connections with many Pacific countries due to migration, travel, and trade. Many of the developing states are characterised by geographical isolation not only within their territory but also from other pacific states. In addition limited resources to promote economic growth, problems with the government infrastructure, to ensure that effective delivery of education and health services are in place, compound the difficulties. The developing tourism industry especially in Samoa, Fiji and the Cook islands is helping to improve the economic stability of these states. An official New Zealand Government report 2009 (1) stated: “Much of the Pacific is making poor progress towards meeting the human development indicators central to reducing poverty and hardship. The challenge is to: *Address basic needs - in Melanesia not all children go to school, many adults are illiterate, and many don't have access to basic health services. * Accelerate economic growth - current growth rates are below population increases in most countries. * Support the rule of law and access to justice, which is essential for poverty reduction.”